1996
DOI: 10.1002/adma.19960080312
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for n‐type conduction in a perylene tetracarboxylic diimide derivative

Abstract: n‐Type—electron transporting—conduction is demonstrated for Schottky diodes and field effect transistors based on N,N′‐diphenyl‐3,4,9,10‐perylenetetracarboxylic‐dimide. The role of the electron‐injecting electrode is discussed, as are the potential improvements in performance offered by devices combining a p‐type semiconducting layer with an n‐type, electron transporting organic compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
220
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(227 citation statements)
references
References 28 publications
3
220
0
4
Order By: Relevance
“…In this context, perylene derivatives stand out due to their suitable optical and electrical properties besides the low cost of processing in comparison to the conventional semiconducting materials [2][3][4][5][6] . Also noteworthy is its high absorption of electromagnetic radiation in the visible and near infrared region 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, perylene derivatives stand out due to their suitable optical and electrical properties besides the low cost of processing in comparison to the conventional semiconducting materials [2][3][4][5][6] . Also noteworthy is its high absorption of electromagnetic radiation in the visible and near infrared region 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] In addition to optical features such as strong absorption in the visible region, high quantum yields and excellent photostability, PBIs also display low reduction potentials, 25 which enables their use as electron-acceptors and n-type semiconductors in photoinduced charge-transfer reactions. For these appealing properties, perylene derivatives have been extensively studied for the fabrication of field-effect transistors, 26 luminescent solar concentrators, 27 dye lasers, 28 photovoltaic cells 29 and organic light-emitting diodes (OLEDs). 30 Researchers tried to identify structure-property relationships of perylene/CNT mixtures in order to provide innovative materials for nanostructured electronic devices and The ability of PZPER molecules to generate π−π stacking interactions has been previously utilized by our group for the preparation of chromogenic plastic materials as temperature indicators.…”
Section: Introductionmentioning
confidence: 99%
“…For example, N , NЈ-diphenyl PTCDI is one of the first n-type organic TFT materials reported by Horowitz et al 16 Recently, Malenfant et al reported that N , NЈ-dioctyl PTCDI exhibited high field-effect electron mobility of ϳ0.6 cm 2 /V s, 12 and then Chesterfield et al also showed the highest field-effect electron mobility in organic semiconducting materials of up to 1.7 cm 2 / V s by finely controlling deposition conditions ͑substrate temperature and deposition rate͒ to attain well organized thin films of the material. 17 It is well known that alkyl chains with -electron cores are effective for self-assembling.…”
mentioning
confidence: 99%